Reforming education and challenging inequalities in southern contexts: research and policy in international development - Rose, Pauline; Arnot, Madeleine; Jeffery, Roger (Abingdon, Oxon : Routledge, 2021)
This book offers in-depth analyses of how education interacts with social inequality in Southern contexts. Drawing on a range of disciplinary frameworks, it presents new analyses of existing knowledge and new empirical data which define the challenges and possibilities of successful educational reform. It is a tribute to the work of the late Christopher Colclough, who, as a leading figure in education and international development, played a key role in the global fight for education for all children. The book critically engages with international evidence of educational access, retention and outcomes, offering new understandings of how social inequalities currently facilitate, mediate or restrict educational opportunities. It exposes the continuing influence of wealth and regional inequalities and caste and gendered social structures. Researchers in Ethiopia, Ghana, India, Pakistan and Uganda highlight how the aspirations of families living in poverty remain unfilled by poor-quality education and low economic opportunities and how schools and teachers currently address issues of gender, disability and diversity. The book highlights a range of new priorities for research and identifies some necessary strategies for education reform, policy approaches and school practice, if educational equality for all children is to be achieved. The book will be of great interest to researchers, scholars, educational practitioners and policy-makers in the fields of economics, politics and sociology of education, international education, poverty research and international development. The Foreword, Chapters 1, 6, 7, and 12 of this book are freely available as downloadable Open Access PDFs at https://www.taylorfrancis.com/books/e/9780429293467 under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license (Foreword, Chapters 1, 6, and 12) and a Creative Commons Attribution 4.0 license (Chapter 7).
Keywords: Educational sociology -- Developing countries -- Cross-cultural studies; Social justice -- Developing countries -- Cross-cultural studies; Educational equalization -- Developing countries -- Cross-cultural studies